Regular exercise combined with ferulic acid exhibits antiobesity effect and regulates metabolic profiles in high-fat diet-induced mice - Wang, Ou; Zhang, Nanhai; Han, Chao; Huang, Jian (Frontiers in Nutrition, 2022)
Exercise (Ex) has been recognized as an effective way for obesity prevention, but it shows a dual effect on the body’s antioxidant system. Ferulic acid (FA) is a kind of phenolic acid with well-known antioxidant capacity and numerous health benefits. Therefore, the aim of the study was to compare the antiobesity effect of Ex, FA, and Ex combined with FA (Ex-FA) in vivo and illustrate the potential mechanisms. Mice were fed with a high-fat diet (HFD) with or without administration of Ex, FA, and Ex-FA for 13 weeks. The body weight, antioxidant ability, Ex performance, and lipid profiles in the serum, liver, and skeletal muscle were compared among the groups, and serum metabolomics analysis was conducted. The results showed that Ex, FA, and Ex-FA exhibited a similar effect on body weight management. Ex could alleviate the HFD-induced dyslipidemia, while FA could mitigate lipid deposition in the liver and skeletal muscle. Ex-FA showed comprehensive effects in regulation of the lipid contents in serum, liver, and skeletal muscle, and provoked enhancement effects on antioxidant ability and Ex capacity. Mice administered with Ex, FA, and Ex-FA showed different metabolic profiles, which might be achieved through different metabolic pathways. The findings of this research implied that Ex coupled with FA could become an effective and safe remedy for the management of dietary-induced obesity.